PENGGUNAAN APLIKASI INKOE CLASS POINT SEBAGAI MEDIA PEMBELAJARAN LURING DALAM UPAYA MENINGKATKAN HASIL BELAJAR PERBAIKAN PERALATAN LISTRIK KELAS XI TKL 2 SEMESTER GASAL 2022/2023 DI SMK NEGERI 1 KLEGO - Tulus Djoko W - SMKN 1 Klego (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2023)
Abstract - This classroom action research aims to increase students' attention and activity while participating in learning to repair electrical equipment using Inkoe Class points and android mobile phones as offline learning media for students in class XI TKL2 SMK Negeri 1 Klego for the 2022/2023 academic year.The research was conducted at SMKN 1 Klego, with research subjects being students of class XI TKL2 SMK Negeri 1 Klego for the 2022/2023 academic year, a total of 36 students. The research was conducted from July 2022 to November 2022. This research is a Classroom Action Research where the researcher is the doer of the action. The research step is a reflection of action with the pattern of